Restructured basic education curriculum implementation in grade one science teaching a case study - Castañares, Aliminda Alao (2007)
This case study was undertaken to look into the content-based instruction of Science in the English subject by two elementary grade teachers in a public school in Davao City. The primary purpose was to find out the problems of teachers in content-based instruction (CBI) integration in grade one and their solutions. The findings of this study include the following: 1. the pupils' attitude towards science CBI is positive 2. the presence of pupils with other cultural affiliations does not affect the implementation of science CBI 3. teachers use both English and Cebuano in imparting concepts while pupils express their ideas using the latter and 4. teachers use their own initiative by researching and internet surfing to look for materials suited for the science CBI.